The Indo-Portuguese creoles of the Malabar: Historical cues and questions - Cardoso, Hugo C. (2020)
THIS ESSAY PROVIDES a state-of-the-art of current research on the Indo-Portuguese creoles of the Malabar. Having been given up as extinct, these creoles have been off the radar of linguists and historians alike for a long while. Yet, they are particularly important as potential descendants of the earliest forms of contact varieties of Portuguese that formed in Asia in the sixteenth century, and raise questions that interact with a social historiography of the Indo-Portuguese communities of the region. This essay will focus on four aspects of the study of these languages which operate on a linguistic-historical interface: (a) the social conditions required for their formation; (b) their course after the end of Portuguese colonial rule; (c) their putative foundational role in the context of Luso-Asian creoles; and (d) the social and linguistic stratification encapsulated in modern and late nineteenth-century records. This discussion is meant as a step towards the integration of linguistic evidence into the study of Indo-Portuguese social history, and of historical evidence into the study of Indo-Portuguese linguistics.